Esophageal Ulcers in Primary Biliary Cholangitis: A Rare Cause of Hematemesis in the Setting of Portal Hypertension and Esophageal Varices - Kolli, Sindhura (Gastroenterology Res, 2018)
Our patient with primary biliary cholangitis, previously termed as primary biliary cirrhosis, presented with an unexpected and unusual cause of hematemesis in the form of multiple esophageal ulcers in-between variceal columns. Given that upon endoscopic examination, the esophageal ulcers were found to bleeding instead of the varices; they should be considered in the differential in the etiology of hematemesis in primary biliary cholangitis and thoroughly searched for during an endoscopic procedure for early treatment and subsequent secondary prevention.